ChemInform Abstract: Organocatalytic Asymmetric One‐Pot Sequential Conjugate Addition/Dearomative Fluorination: Synthesis of Chiral Fluorinated Isoxazol‐5(4H)‐ones. Issue 21 (2nd May 2013) - Meng, Wen‐Ting; Zheng, Yan; Nie, Jing; Xiong, Heng‐Ying; Ma, Jun‐An
Abstract By using the bifunctional chiral tertiary amino‐thiourea catalyst STC, a series of chiral fluorinated isoxazol‐5(4H)‐ones containing a fluorine‐substituted quarternary stereocenter are obtained in high yields with high enantio‐ and diastereoselectivities.